Chronic MK-801 Application in Adolescence and Early Adulthood: A Spatial Working Memory Deficit in Adult Long-Evans Rats But No Changes in the Hippocampal NMDA Receptor Subunits - Uttl, Libor; Petrasek, Tomas; Sengul, Hilal; Svojanovska, Marketa; Lobellova, Veronika; Vales, Karel; Radostova, Dominika; Tsenov, Grygoriy; Kubova, Hana; Mikulecka, Anna; Svoboda, Jan; Stuchlik, Ales (Frontiers in Pharmacology, 2018)
The role of NMDA receptors in learning, memory and hippocampal function has long been recognized. Post-mortem studies have indicated that the expression or subunit composition of the NMDA glutamate receptor subtype might be related to the impaired cognitive functions found in schizophrenia patients. NMDA receptor antagonists have been used to develop animal models of this disorder. There is accumulating evidence showing that not only the acute but also the chronic application of NMDA receptor antagonists may induce schizophrenia-like alterations in behavior and brain functions. However, limited evidence is available regarding the consequences of NMDA receptor blockage during periods of adolescence and early adulthood. This study tested the hypothesis that a two-week treatment of male Long-Evans and Wistar rats with dizocilpine (MK-801; 0.5 mg/kg daily) starting at postnatal days (PD) 30 and 60 would cause a long-term cognitive deficit and changes in the levels of NMDA receptor subunits. The working memory version of the Morris water maze (MWM) and active place avoidance with reversal on a rotating arena (Carousel) requiring cognitive coordination and flexibility probed cognitive functions and an elevated-plus maze (EPM) was used to measure anxiety-like behavior. The Western blot method was used to determine changes in NMDA receptor subunit levels in the hippocampus. Our results showed no significant changes in behaviors in Wistar rats. Slightly elevated anxiety-like behavior was observed in the EPM in Long-Evans rats with the onset of treatment on PD 30. Furthermore, Long-Evans rats treated from PD 60 displayed impaired working memory in the MWM. There were; however, no significant changes in the levels of NMDA receptor subunits because of MK-801 administration. These findings suggest that a two-week treatment starting on PD 60 in Long-Evans rats leads to long-term changes in working memory, but this deficit is not paralleled by changes in NMDA receptor subunits. These results support the face validity, but not construct validity of this model. We suggest that chronic treatment of adolescent and adult rats does not constitute a plausible animal model of schizophrenia.